2018 IEEE International Conference on Bioinformatics and Biomedicine (BIBM) 2018
DOI: 10.1109/bibm.2018.8621484
|View full text |Cite
|
Sign up to set email alerts
|

Opening the Black Box: Discovering and Explaining Hidden Variables in Type 2 Diabetic Patient Modelling

Abstract: Clinicians predict disease and related complications based on prior knowledge and each individual patient's clinical history. The prediction process is complex due to the existence of unmeasured risk factors, the unexpected development of complications and varying responses of patients to disease over time. Exploiting these unmeasured risk factors (hidden variables) can improve the modeling of disease progression and thus enables clinicians to focus on early diagnosis and treatment of unexpected conditions. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…This section summarises the clinical implications and shows how the obtained experimental findings in the previous works [83,84,97] and their significance have led to developing explanatory AI models. For example Table 3 illustrated the promising results obtained by the proposed Stepwise approach discussed in [33,84].…”
Section: Experimental Results and Conclusionmentioning
confidence: 91%
See 2 more Smart Citations
“…This section summarises the clinical implications and shows how the obtained experimental findings in the previous works [83,84,97] and their significance have led to developing explanatory AI models. For example Table 3 illustrated the promising results obtained by the proposed Stepwise approach discussed in [33,84].…”
Section: Experimental Results and Conclusionmentioning
confidence: 91%
“…Among these, studies on explaining unknown risk factors and identifying temporal phenotypes by using hybrid methods (including descriptive and predictive) are rare to find in literature. It represented the reason of the earlier research conducted by the author in [32,33,[83][84][85]. The current work of this chapter's author has attempted to address these issues in the previous research in [32,33,84], after describing the case study data as a starting point, the suggested methodology is explored as a framework for modelling real time-series clinical data.…”
Section: The Suggested Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…We developed methods to infer the location of hidden variables within these models in order to improve prediction 2 . The behavior of these hidden variables over the course of the disease process can be thought of as a “temporal phenotype” for an individual patient, 3 which is considered as a “latent phenotype.”…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, an intuitive stepwise method to learn the latent effects was developed based upon the IC* algorithm, while using a Pair-Sampling re-balancing method [23]. In [24][25][26], patients were clustered into different sub-groups. In each sub-group, they shared a similar profile of observed risk factors, without taking account of the cluster decision making process.…”
Section: Introductionmentioning
confidence: 99%